Efektivitas Konsultasi dan Pengaduan Pelayanan Publik melalui Whatsapp oleh Dinas Kependudukan dan Pencatatan Sipil Kabupaten Bintan - Ananda, Almar; Nur Kahana, Kartini; Sholeh, Chaereyranba (Policy, Law and Political Research Center, 2023)
The focus of this research is to find out the effectiveness of public service complaints consultation via whatsapp by the Bintan Regency population and civil registration office. The methodology used is qualitative and uses descriptive research methods with a qualitative research approach and the data used are primary and secondary data. The results of this study indicate that the effectiveness of consultation on public service complaints via whatsapp by the Bintan Regency population and civil registration service is in accordance with established procedures with a Community Satisfaction Index of 87%. Therefore, it is hoped that the results of this study can provide positive results for the Bintan Regency population and civil registration service.